Product market competition and disclosure deficiencies in different mandatory filing types: Evidence from SEC comment letters - Ahn, J.H.; Chung, H. (Research in International Business and Finance, 2025)
Using firms’ receipt of SEC comment letters, this study investigates their selection of mandatory filing types when producing deficient disclosures in response to the product market competition. Empirical evidence reveals a positive association between two firm-level measures of product market competition and a firm's likelihood of receiving comment letters for non-10-K filings. These patterns are particularly pronounced when firms face a higher likelihood of new market entrants or operate as industry followers. Additionally, firms receiving comment letters for non-10-K filings experience increased sales and market share in the subsequent year. Overall, these findings suggest that firms strategically make deficient disclosures in non-10-K filings to minimize regulatory costs. © 2024 Elsevier B.V.
Keywords: Disclosure deficiency; Mandatory disclosure; Product market competition; Proprietary cost; SEC comment letters; dept.acc; peer-reviewed

Instructional models for course-based research experience (CRE) teaching - Hanauer, D.I.; Graham, M.J.; Arnold, R.J.; Ayuk, M.A.; Balish, M.F.; Beyer, A.R.; Butela, K.A.; Byrum, C.A.; Chia, C.P.; Chung, H.-M.; Clase, K.L.; Conant, S.; et al. (CBE life sciences education, 2022)
The course-based research experience (CRE) with its documented educational benefits is increasingly being implemented in science, technology, engineering, and mathematics education. This article reports on a study that was done over a period of 3 years to explicate the instructional processes involved in teaching an undergraduate CRE. One hundred and two instructors from the established and large multi-institutional SEA-PHAGES program were surveyed for their understanding of the aims and practices of CRE teaching. This was followed by large-scale feedback sessions with the cohort of instructors at the annual SEA Faculty Meeting and subsequently with a small focus group of expert CRE instructors. Using a qualitative content analysis approach, the survey data were analyzed for the aims of inquiry instruction and pedagogical practices used to achieve these goals. The results characterize CRE inquiry teaching as involving three instructional models: 1) being a scientist and generating data; 2) teaching procedural knowledge; and 3) fostering project ownership. Each of these models is explicated and visualized in terms of the specific pedagogical practices and their relationships. The models present a complex picture of the ways in which CRE instruction is conducted on a daily basis and can inform instructors and institutions new to CRE teaching.
Keywords: Educational; Engineering; Faculty; Humans; Mathematics; Models; Students; Teaching; dept.bio; educational model; engineering; human; mathematics; peer-reviewed; student; teaching; university